QUEERING DIGITAL LITERATURE AND DIGITAL WELL-BEING IN JEFF GARVIN’S SYMPTOMS OF BEING HUMAN - Sapuh, Semhayi; Das, Nigamananda (ShodhGyan-NU: Journal of Literature and Culture Studies, 2024)
The development of digital technology and communication has brought about rapid transformation in the field of literature. Books, articles, blog posts, tweets, and conferences, that constitute the digital humanities have grown exponentially in the 21st century. The emergence of the digital space has received a quick response from various literary genres, and in no exception, queer literature, which ranges from online book publications to documenting queer experiences through blogs and more generic social networking sites like Facebook and Instagram, has not only become a popular and affordable space for the queer community but more than a socializing space across the globe. Queer literature on digital space can now be seen as the fastest-growing genre of literature that evolved. Jeff Garvin’s Symptoms of Being Human, which is written in the form of blog posts, explores the way in which this digital space has provided an opportunity for queer literature and the community to thrive by curating their identities online, reaching out to like-minded people across the globe, documenting their experiences, and educating the public about their unacknowledged identity and sexuality. The paper examines how this new mode of communication paved the way for digital well-being by maintaining a balance between the digital and the real world, accommodating and acculturating social space, acting morally and responsibly, and effectively managing digital and real-life interactions, as demonstrated in Jeff Garvin’s Symptoms of Being Human.